Season, Body Condition and Developmental Stage Influence the Gut Microbiota of the Sole Living Rhynchocephalian Reptile (Sphenodon punctatus) - Carmen Hoffbeck; Danielle M. R. L. Middleton; Nicola J. Nelson; Michael W. Taylor (Ecology and Evolution, 2025)
ABSTRACT Seasonality plays a crucial role for many species, especially reptiles. In multiple reptile species, seasonality has been linked to shifts in the gut microbiota, influenced by factors, such as ambient temperature, food availability and shifting host function across different seasons. We tested whether the tuatara, an endemic New Zealand reptile and the sole extant member of the order Rhynchocephalia, maintains a stable gut microbiota over 2 years of sampling across three seasons (summer, autumn, spring) or if the dominant bacterial community varies with season. We found that community diversity changed significantly seasonally, with the most diverse gut community found in the spring. We also found that season significantly influenced beta‐diversity, as did tuatara developmental stage, tuatara body condition and tick abundance. However, there was little evidence for a recurring seasonal bacterial assemblage in 2024 compared with 2023. For tuatara where the same individual was resampled over multiple seasons, bacterial community composition appeared to be most correlated with the time of sampling, with closer temporal samples more similar to one another than samples taken further apart, which was also seen in the significance of the sampling period as a factor explaining variation across all tuatara. We identified bacterial genera that significantly increased or decreased in each season. Despite notable shifts among seasons, particularly in autumn, the tuatara gut microbiota exhibits remarkable persistence over time, including within individuals.